Milfruto - Nueva variedad de Chile Dulce - Casseres, E.; Thomas, N. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A new variety of sweet pepper, Capsicum frutescens, has been produced by the Inter-American Institute of Agricultural Sciences. Because of its high productivity it has been named Milfruto, or thousand-fruit. Selections were initiated in 1947 from individual plants of native pepper in a local planting showing considerable heterogeneity. The plants average 75 centimeters in height, grow vigorously, and produce for a relatively long period. The fruits average 7.3 centimeters in length and 6.1 in width at the widest part. The initial harvest can be made 10 weeks after planting and harvesting continued two or three times a week for eight weeks. About two months later a second, smaller harvest can be made. In the various field trials conducted in Trinidad, six improved lines of Milfruno yielded consistently higher than any of 18 imported varieties. While average production of the imported varieties was 2 to 3 peppers per plant, the Milfruno lines produced from 5 to 10. California Wonder gave the best results among the imported varieties. Milfruno lines also showed considerably more resistance to the diseases prevalent.